Leaf and Root Extracts from Campomanesia adamantium (Myrtaceae) Promote Apoptotic Death of Leukemic Cells via Activation of Intracellular Calcium and Caspase-3 - Jaqueline F. Campos; Priscilla P. de Toledo Espindola; Heron F. V. Torquato; Heron F. V. Torquato; Wagner D. Vital; Giselle Z. Justo; Giselle Z. Justo; Denise B. Silva; Carlos A. Carollo; Kely de Picoli Souza; Edgar J. Paredes-Gamero; Edgar J. Paredes-Gamero; et al. (Frontiers Media S.A., 2017)
Phytochemical studies are seeking new alternatives to prevent or treat cancer, including different types of leukemias. Campomanesia adamantium, commonly known as guavira or guabiroba, exhibits pharmacological properties including antioxidant, antimicrobial, and antiproliferative activities. Considering the anticancer potential of this plant species, the aim of this study was to evaluate the antileukemic activity and the chemical composition of aqueous extracts from the leaves (AECL) and roots (AECR) of C. adamantium and their possible mechanisms of action. The extracts were analyzed by LC-DAD-MS, and their constituents were identified based on the UV, MS, and MS/MS data. The AECL and AECR showed different chemical compositions, which were identified as main compounds glycosylated flavonols from AECL and ellagic acid and their derivatives from AECR. The cytotoxicity promoted by these extracts were evaluated using human peripheral blood mononuclear cells and Jurkat leukemic cell line. The cell death profile was evaluated using annexin-V-FITC and propidium iodide labeling. Changes in the mitochondrial membrane potential, the activity of caspases, and intracellular calcium levels were assessed. The cell cycle profile was evaluated using propidium iodide. Both extracts caused concentration-dependent cytotoxicity only in Jurkat cells via late apoptosis. This activity was associated with loss of the mitochondrial membrane potential, activation of caspases-9 and -3, changes in intracellular calcium levels, and cell cycle arrest in S-phase. Therefore, the antileukemic activity of the AECL and AECR is mediated by mitochondrial dysfunction and intracellular messengers, which activate the intrinsic apoptotic pathway. Hence, aqueous extracts of the leaves and roots of C. adamantium show therapeutic potential for use in the prevention and treatment of diseases associated the proliferation of tumor cell.